The Effect of Delayed Oncology Surgery on Survival Outcomes for Patients With Gastric Cancer During the COVID-19 Pandemic: Evidence-Based Strategies - Ma, Jichun; Zhu, Chenglou; Li, Weidong; Qiu, Zhisheng; Yang, Jian; Ge, Long; Da, Mingxu (Frontiers in Oncology, 2022)
Objective To evaluate the impact of delay in gastrectomy on gastric cancer patients’ survival outcomes during the COVID-19 pandemic. Methods Databases including PubMed, MEDLINE (using the Ovid platform), Embase, the Cochrane Library, COVID-19 Open Research Dataset Challenge, COVID-19 Research Database (WHO), ClinicalTrials.gov, and WHO International Clinical Trials Registry Platform were searched for studies of any design and in any setting that included patients with gastric cancer from their inception to July 31, 2021. Hazard ratio (HR) and 95% confidence intervals (CI) of research endpoints in each study were calculated. Statistical analyses were performed with Stata 12.0. Results A total of 8 studies involving 4,052 gastric cancer patients were eligible and included in the present meta-analysis. The result of the meta-analysis was shown that delaying surgery for less than 8 weeks may not decrease OS (HR = 0.91, 95% CI: 0.80 1.04, p = 0.167) and DFS (HR = 0.96, 95% CI: 0.62 1.50, p = 0.872) in gastric cancer. Our meta-analysis also illustrated that delay in surgery for more than 4 weeks (HR = 0.85, 95% CI: 0.56 1.27, p = 0.421), 6 weeks (HR = 0.88, 95% CI: 0.61 1.27, p = 0.490), and 8 weeks (HR = 0.93, 95% CI: 0.80 1.07, p = 0.314) was also not associated with a decreased OS. Conclusion A delay in surgery of less than 8 weeks is not associated with worse overall survival for patients with gastric cancer.